Bronchoscopy for Chronic Unexplained Cough: Use of Biopsies and Cultures Increase Diagnostic Yield. Issue 1 (January 2020) - Heching, Moshe; Rosengarten, Dror; Shitenberg, Dorit; Shtraichman, Osnat; Abdel-Rahman, Nader; Unterman, Avraham; Kramer, Mordechai R.
Abstract : Background: Prior studies assessing the diagnostic utility of bronchoscopy for chronic unexplained cough have focused primarily on identifying endobronchial anomalies to determine chronic cough etiology. On the basis of our institutional experience, expanding bronchoscopy to include cultures and biopsies can considerably increase its diagnostic yield for identifying the etiology of chronic unexplained cough. Materials and Methods: This retrospective review analyzed bronchoscopies conducted in our institution between 2013 and 2017. Eligibility criteria were bronchoscopies conducted for chronic unexplained cough for which no etiology had been identified before the bronchoscopy. Microbiology, pathology, and cytology results from bronchoscopy were reviewed to identify the etiology of the cough. Results: Over the study period, 169 bronchoscopies met the eligibility criteria. The average patient age at bronchoscopy was 59.7±14.8 years; 61% were female individuals. Direct visualization identified anatomic etiologies in 48 (28%) patients, most commonly tracheobronchomalacia, and less common conditions, such as tracheobronchopathia osteochondroplastica. Microbiology cultures were positive in 33 (20%) patients, principally Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, and nontuberculosis mycobacterium. Pathology results from endobronchial biopsies identified respiratory conditions associated with cough, primarily eosinophilic bronchitis (n=15), as well as neurofibromatosis (n=1) and amyloidosis (n=1). Cytology results did not reveal alternate diagnoses not previously identified. Conclusion: Inclusion of bronchial washings and endobronchial biopsies during bronchoscopy for chronic unexplained cough increased diagnostic yield from 28%, attributable to directly visualized anatomic etiologies, to 41%. The addition of microbiology cultures and pathology analysis significantly increased the diagnostic yield of bronchoscopy in identifying the potential etiology of chronic heretofore unexplained cough.